Pengembangan Aplikasi Web Pariwisata Berbasis Progressive Web App untuk Meningkatkan Pengalaman Wisatawan - Shaquille Akbar Demsi; Laila Isyriyah; Paradise Paradise; Rakhmad Maulidi (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
The development of information technology has brought significant changes to the tourism industry, yet challenges remain in developing comprehensive and accessible tourism web applications. This research aims to develop a multi-platform tourism web application that addresses the fragmentation of information services and trip planning, as well as accessibility limitations in destinations with limited connectivity. The research methodology includes system design using an agile approach with Scrum methodology, implementation of key features such as trip planning and article writing, and comprehensive testing through functional and acceptance testing. Implementation of Progressive Web Apps (PWA) and Trusted Web Activities (TWA) technologies is integrated to enhance accessibility and user experience. Test results show a success rate of nearly 100% in various usage scenarios, including offline conditions. The main conclusion demonstrates that the developed application successfully creates a digital ecosystem supporting holistic travel experiences, transforming how travelers plan, experience, and share their journeys. This research paves the way for innovation in leveraging web technology to improve accessibility of tourist destinations, support local economies, and promote sustainable tourism, with significant potential to transform the landscape of the digital tourism industry.